Analgesic effects and metabolome analyses of laser- and electro-acupuncture combined therapies in paclitaxel-induced neuropathic pain model - Yoon, Chan-Suk; Lee, Ga-Won; Kim, Myeong-Hun; Kang, Sang-Mi; Youn, Cha-Kyung; Yang, Ji-Hye; Kim, Eun-Ju; Son, Hong-Seok; Pak, Sok Cheon; Kim, Seon-Jong; Na, Chang-Su (Frontiers in Veterinary Science, 2023)
Allodynia, which can be induced by paclitaxel administration, is the presence of pain as a result of a stimulus that does not usually provoke pain. Many studies have investigated the analgesic efficacy of acupuncture, including laser acupuncture (LA) and electroacupuncture (EA). Although pain-related diseases are relatively common, few studies have analyzed the analgesic effects and mechanisms of LA combined with EA. The purpose of this study was to investigate the therapeutic effect and mechanism of manual acupuncture (MA), EA, LA, and combined therapy (LA+EA) in a paclitaxel-induced allodynia rat model. A total of 56 rats were classified into eight groups: a normal (Nor, n = 7), a control (Con, n = 7), an MA (n = 7), an EA (n = 7), a 650-nm LA (650LA, n = 7), an 830-nm LA (830LA, n = 7), a 650-nm LA combined with EA (650LA+EA, n = 7), and an 830-nm LA combined with EA group (830LA+EA, n = 7). Allodynia was induced by intraperitoneal injection of 2 mg/kg of paclitaxel every other day for a total of four times except the Nor group. Acupuncture treatments were conducted at the points of Jungwan (CV12) and Joksamni (ST36) once every other day for 6 minutes, for a total of nine times. Withdrawal response reaction times and force intensity of the foot were measured before the start of the experiment, after the 4th paclitaxel administration (day 8), and after the 9th and last treatment (day 15). On the 16th day, mRNA and protein expression in the spinal nerves was assessed, and a metabolome analysis of the animals’ feces was performed. Our analyses show that 650LA+EA treatment resulted in an upregulation of protein expression related to pain relief and nerve regeneration, whereas 830LA+EA treatment led to significant changes in metabolomes. This study demonstrates that a combination treatment of EA and LA can suppress allodynia and promote upregulation of protein expression related to nerve regeneration and is effective in changing the intestinal microbiome. Further large-scale research is required to assess the exact mechanism underlying the therapeutic effect of this combination treatment in pain-related diseases.